A qualitative study investigating the decision-making process of women’s participation in marital infidelity - Marchese Jeanfreau, Michelle (Kansas State University, 2009)
This study used a qualitative approach as a means of exploring the decision-making process of women's participation in marital infidelity. Due to the growing prevalence and negative effects of marital infidelity, it is important for both clinicians and researchers to understand its occurrence. Although there has been a significant amount of research on marital infidelity in recent years, there is not any significant research that looks at the process occurring in both the marital and extramarital relationships. This study focused on examining the process an individual goes through when making the decision to have an affair, particularly, how they were able to give themselves permission to have an affair. Semi-structured interviews were conducted with four female participants who had participated in marital infidelity. The interviews were audio taped, transcribed, and analyzed using the transcendental phenomenological model (Moustakas, 1994). Four categories and 14 themes emerged, regarding the decision-making and permission-giving processes of women’s participation in marital infidelity. The women reported a lack of quality time spent with their husbands, as well as a lack of attention they received from their husbands. The women also discussed an inability to solve conflict within their marriage. The women reported developing relationships, outside of their marriage, either with ex-flames, old friends, or new friends, all of whom became their affair partner. The women reported the support of family and/or friends for the extramarital relationship, along with receiving positive attention from their affair partner. The women discussed the moral values as being a deterrent to marital infidelity, but did not perceive enough barriers or protective factors as preventing them from moving forward with the affair. Finally, the women described ways in which they were able to limit cognitive dissonance as a means of giving themselves permission to move forward with the affair. Clinical and research implications were discussed, as well as, the limitations of the current study.
Keywords: Marital infidelity; process; qualitative; decision-making; permission-giving; Psychology, Clinical (0622)